The Effect of Knowledge on Implementation Interest through Actual Behavioral Control - Hanifah Fauziah; Asep Mulyana; Thomas Budhyawan Yudhya (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
This study aims to analyze the Carrington model in shaping the actual buying behavior of coffee in Garut Regency. This research was conducted because of the gap between intention and actual purchase behavior. The quantitative survey method was used to analyze the variables of knowledge, interest in implementation, and actual behavioral control. Researchers collected data through observation, distributing questionnaires, and documentation. Questionnaires in this study were administered online and offline to coffee consumers. The number of consumers studied was 400 respondents. Researchers analyzed the data using cluster analysis tools with SPSS 25.0 tools and SEM-PLS with smartPLS. The results of hypothesis testing show that knowledge has an effect on implementation interest through actual behavioral control.